Detection of Multiresistance Tuberculosis in the Surrounding of Tuberculosis Patients with Multiresistant Bacillus in Kinshasa (DRC) - B.M.J., Kabedi; K., Taba; N.J.M., Kayembe; K.P., Kayembe; M.O., Lunguya; F.S., Bisuta; K.P., Mbaya; T.J.J., Muyembe (International Journal of Innovative Research in Medical Science, 2018)
Context - Diagnosis and early treatment of MDR-TB in contact cases is a major challenge in hope to reduce the burden of morbidity and mortality due to this condition. Objectives - The objective was to assess the prevalence of drug-resistant TB and to compare the phenotypic and genotypic profile of the contact case with that of the index. Material and Methods - Prospective cohort study of 240 household contacts of 59 MDR-TB cases diagnosed and having a positive Ziehl at Elonga, St Alphonse and CUK CSDT was carried out from July 1, 2011 to August 28, 2013. Two sputum specimens were examined in each suspected tuberculosis contact for Ziehl-Neelsen's Koch bacillus and cultured for susceptibility testing on Lowensten-Jensen medium. The tuberculin test was performed on each contact and the spoligotyping of the index of contact cases was performed to determine whether the strains were epidemiologically linked. Results - Twenty-nine contacts out of 240 (12.1%) had symptoms suggestive of tuberculosis and 29 strains of Mycobacterium were isolated from 18 HIV-positive and 11 HIV-negative patients. The identification of these strains shows 26 Mycobacterium. tuberculosis and 6 Mycobacterium africanum. Of these contacts, 23 had a positive Ziehl and 6 had a negative IDR and Ziehl with positive HIV status. The antibiogram performed shows 16 resistant strains at least to one antituberculosis drug. MDR-TB (6.3%) and among them 4.2% preXDR (10) and 0.4% XDR-TB were detected. The phenotypic profile of 15 strains of the contacts corresponded to that of the index case and among the 8 typed strains, six were identical to the source case and 2 had a different profile. Conclusion - The survey determined the prevalence of TB and MDR-TB among the index case contacts. The high proportion reported in this survey is reminiscent of the WHO's alarm bell for early detection to halt the spread of the disease in the population.